Benefits, barriers, and levels of e-commerce adoption: study of traditional beverage SMEs - Nuning Setyowati; Masyhuri; Jangkung Handoyo Mulyo; Irham (Agricultural and Resource Economics, 2024)
Purpose. This study analyses the perceived benefits and barriers of e-commerce use by traditional micro, small, and medium beverage enterprises (SMEs). The research also identifies the level of e-commerce adoption by SMEs and further analyses the effect of benefits and barriers on e-commerce adoption levels in traditional beverage SMEs.